110 Post-transcriptional regulation of trib1 by mirnas in primary macrophages. (June 2018) - Niespolo, Chiara; Viloria, Juan Salamanca; Perez, Oscar Villacanas; Wilson, Heather; Kiss-Toth, Endre
Abstract : Background: The TRIB1 gene has been linked to several human pathologies, including lipid disorders and cardiovascular disease. It has also been established that it critically regulates M2-like macrophage differentiation and unpublished data from our group links its expression to increased atherosclerotic plaque formation. Previous studies reported that TRIB1 protein is produced from a highly unstable mRNA, with a half-life shorter than 1 hour, suggesting it may be subject to post-transcriptional regulation. Indeed, the TRIB1 transcript includes a long, conserved 3'UTR, enriched with miRNA-binding sites. This study aims to investigate the post-transcriptional regulation of TRIB1 by miRNAs in the context of macrophage biology. Macrophages have been implicated in immune- and cardio-metabolic diseases; controlling their molecular responses through the activity of miRNAs and TRIB1 may represent an attractive therapeutic approach. Methods miRanda3.2 algorithm was used to predict miRNAs targeting TRIB1. Additional tools and online databases were used to identify macrophage-specific miRNAs. To experimentally validate predicted interactions, a dual luciferase reporter assay was performed in HEK293T cells, followed by RT-qPCR and western blotting analysis of human monocytes-derived macrophages (MDMs) to quantify endogenous TRIB1 mRNA and protein changes, upon miRNA overexpression. Results: We found that TRIB1 mRNA is a potential target of multiple different miRNAs not only via the canonical 3'UTR but also via the 5'UTR and CDS (n. of putative interactions=1745; n. of distinct miRNAs=1145); several miRNAs potentially targeting TRIB1 have been previously reported to impact macrophage pro- and anti-inflammatory responses. Among them, miR-101–3 p was tested in a luciferase assay and was found to impair the reporter gene activity. In addition, overexpressing miR-101–3 p in MDMs, resulted in a decrease in endogenous TRIB1 mRNA levels (>50%), suggesting that miR-101–3 p is a novel regulator of TRIB1. Conclusions: These findings support the notion that TRIB1 mRNA instability may be due to miRNA-mediated silencing mechanisms; specifically the miR-101–3 p/TRIB1 interaction may regulate macrophage polarisation and function.